Characterization of children and adolescents with psychosis risk syndrome: The Children and Adolescents Psychosis Risk Syndrome (CAPRIS) study. Issue 5 (26th November 2018) - Dolz, Montserrat; Tor, Jordina; De la Serna, Elena; Pardo, Marta; Muñoz‐Samons, Daniel; Rodríguez‐Pascual, Marta; Puig, Olga; Sugranyes, Gisela; Usall, Judith; Sánchez‐Gistau, Vanessa; Baeza, Inmaculada
Abstract : Aim: Despite the interest in psychosis risk syndrome (PRS) in children and adolescents, information on the syndrome in this population is scarce. Methods: Prospective naturalistic multi‐site study in which 10‐ to 17‐year‐old help‐seeking subjects who met PRS criteria (positive or negative attenuated symptoms; brief limited intermittent psychotic symptoms; genetic risk or schizotypal personality disorder plus impairment in functioning) were included, along with 45 age and sex‐matched healthy controls (HC). All subjects were clinically and functionally assessed. Results: Ninety‐one PRS subjects (PRSS) with a mean age of 15.5 ± 1.4 met inclusion criteria (IC). Compared with HC, PRSS presented worse global and academic functioning in the previous year, had experienced more psychiatric and psychological problems, and presented gestational ages outside the normal range. More than 80% of PRSS met ≥2 IC, with 65.9% having one Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition Text Revision diagnosis, and 61.7% of those having ≥2 diagnoses. Some 49.5% of PRSS had a first‐ or second‐degree family history (FH) of psychosis. Patients with first‐ and second‐degree FH do not differ in their clinical expression. Conclusions: Children and adolescents with PRS are a patient group with a pattern of neurodevelopmental impairment and clinical complexity similar to patients with schizophrenia spectrum disorders, highlighting the importance of assessing these variables in child and adolescent samples. PRSS with first‐ and second‐degree relatives with FH do not present differences in their clinical presentation, suggesting that including these two groups of patients in the genetic risk criteria would enrich knowledge of these criteria.